2014
DOI: 10.18632/oncotarget.2731
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid overcomes chemoresistance and immunosuppression of malignant mesothelioma

Abstract: The human malignant mesothelioma (HMM) is characterized by a chemoresistant and immunosuppressive phenotype. An effective strategy to restore chemosensitivity and immune reactivity against HMM is lacking. We investigated whether the use of zoledronic acid is an effective chemo-immunosensitizing strategy.We compared primary HMM samples with non-transformed mesothelial cells.HMM cells had higher rate of cholesterol and isoprenoid synthesis, constitutive activation of Ras/extracellular signal-regulated kinase1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…2 The MPM microenvironment is rich of immunosuppressive and anergic immune cells, such as T-regulatory (Treg), granulocytic, and monocytic myeloid-derived suppressor cells (Gr-MDSC/Mo-MDSC) and M2-polarized tumor associated macrophages (TAMs), thattogether with soluble factors, such as cytokines, chemokines, and kynurenine, the product of 2,3-indoleamine dioxygenase enzymelead to a poor response to immune therapy. [3][4][5][6][7][8][9] Several cytokines accumulated in the pleural effusion of MPM patients promote the M2 polarization of macrophages. 10,11 M2/M3-macrophages and Gr-MDSC of MPM patients, as well as MPM cells reduce the proliferation of heterologous CD8a molecule-positive (CD8 þ ) T lymphocytes, by producing immunosuppressive mediators such as reactive oxygen species (ROS), nitric oxide (NO) and kynurenine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The MPM microenvironment is rich of immunosuppressive and anergic immune cells, such as T-regulatory (Treg), granulocytic, and monocytic myeloid-derived suppressor cells (Gr-MDSC/Mo-MDSC) and M2-polarized tumor associated macrophages (TAMs), thattogether with soluble factors, such as cytokines, chemokines, and kynurenine, the product of 2,3-indoleamine dioxygenase enzymelead to a poor response to immune therapy. [3][4][5][6][7][8][9] Several cytokines accumulated in the pleural effusion of MPM patients promote the M2 polarization of macrophages. 10,11 M2/M3-macrophages and Gr-MDSC of MPM patients, as well as MPM cells reduce the proliferation of heterologous CD8a molecule-positive (CD8 þ ) T lymphocytes, by producing immunosuppressive mediators such as reactive oxygen species (ROS), nitric oxide (NO) and kynurenine.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 M2/M3-macrophages and Gr-MDSC of MPM patients, as well as MPM cells reduce the proliferation of heterologous CD8a molecule-positive (CD8 þ ) T lymphocytes, by producing immunosuppressive mediators such as reactive oxygen species (ROS), nitric oxide (NO) and kynurenine. 3,4,7,10,[12][13][14] MDSCs are killed by active CD8 þ T lymphocytes, whereas either Tregs and MDSCs reduce CD8 þ T lymphocyte activity and memory CD8 þ T lymphocyte recruitment, inducing a vicious immunosuppressive circle. 4,6,[15][16][17][18] The high expression of immune checkpoints on T lymphocytes and of their ligands on MPM cell has another crucial role in the MPM-induced anergy of tumor-infiltrating lymphocytes (TILs).…”
Section: Introductionmentioning
confidence: 99%
“…[38, 39] In this study, we showed that ZA inhibited the proliferation and chemotactic migration of Treg cells, thereby improving the antitumor immune response. Recently, Ghigo et al found a similar effect of ZA, which down-regulated indoleamine 1,2 dioxygenase and enabled the proliferation of T cells and inhibited the expansion of Treg cells [40]. …”
Section: Discussionmentioning
confidence: 99%
“…First, ABCB1 limits the intracellular concentration of doxorubicin necessary to induce cell death. Second, ABCB1 inhibits the immune-sensitizing function of calreticulin [9,10]. The pharmacological inhibitors of ABCB1 did not reach satisfactory clinical efficacy, because of poor specificity and high toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting signaling pathways up-regulating ABCB1 is an attractive alternative to inhibit this undruggable protein. For instance, lowering cholesterol and isoprenoid-dependent pathways decreases ABCB1 and produces chemo-immune-sensitization in different solid tumors [9,10].…”
Section: Introductionmentioning
confidence: 99%